Industrialization and communism: the Portuguese Communist Party confronts the Sines growth pole - Patrício, M. T. (Journal of Communist Studies, 1990)
Sines, a small fishing town on the southern coast of Portugal, was chosen in the early 1970s as the site of a large state-led industrial growth pole project. By focusing on the role of the local Portuguese Communist Party organization in the confrontation of this traditional community with large-scale rapid industrialization, the process whereby community interests become linked to communist representation can be studied. Changing forms of the state and community exclusion from the industrial project help explain this relationship.